2003
DOI: 10.1099/jmm.0.04972-0
|View full text |Cite
|
Sign up to set email alerts
|

`Genotypic shuffling’ of sequential clones of Candida albicans in HIV-infected individuals with and without symptomatic oral candidiasis

Abstract: Although HIV-infected individuals harbour multiple strains of oral Candida albicans, little is known of their micro-evolution over time. Therefore, a prospective study was conducted with 16 HIV-infected ethnic Chinese individuals with and without symptoms of oropharyngeal candidiasis to evaluate the genotype distribution of oral C. albicans isolates during HIV disease progression. Oral-rinse samples were obtained from all individuals and up to five C. albicans colonies were selected for each visit, over a 12 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
25
1
11

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 50 publications
2
25
1
11
Order By: Relevance
“…Some surveys of oral isolates have shown the same strain persisting for months to years (4,17). Occasionally, authors have suggested that multiple strain types coexist in samples from some patients (27,69,83), but such findings are in the minority and may reflect technical sensitivities and variabilities in the typing methodologies used in some cases. The epidemiology of disseminated C. albicans infection has been studied much less often than that of superficial sites, but the results of surveys based on karyotype electrophoretic patterns (62,63,93), randomly amplified PCR fragments (92), DNA fingerprinting with oligonucleotide probes (44,67), and multilocus enzyme electrophoresis (12) consistently indicate that isolates from blood are highly similar to, or indistinguishable from, isolates from superficial sites in the same patient.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Some surveys of oral isolates have shown the same strain persisting for months to years (4,17). Occasionally, authors have suggested that multiple strain types coexist in samples from some patients (27,69,83), but such findings are in the minority and may reflect technical sensitivities and variabilities in the typing methodologies used in some cases. The epidemiology of disseminated C. albicans infection has been studied much less often than that of superficial sites, but the results of surveys based on karyotype electrophoretic patterns (62,63,93), randomly amplified PCR fragments (92), DNA fingerprinting with oligonucleotide probes (44,67), and multilocus enzyme electrophoresis (12) consistently indicate that isolates from blood are highly similar to, or indistinguishable from, isolates from superficial sites in the same patient.…”
mentioning
confidence: 98%
“…Most work of this nature has confirmed a tendency towards the persistence of a unique strain in each human host, which was suggested even in the earliest studies based on phenotypic strain typing (45,53). Minor variations in genetically determined strain types in surveys of multiple C. albicans isolates from individual patients have been described as "microevolution" (33,35,37,64,65,76,78) or genotypic shuffling (37,69). (This is not the usual sense in which the term "microevolution" is used by population geneticists.)…”
mentioning
confidence: 99%
“…In contrast, few authors have suggested that multiple strain types may coexist in the same clinical sample from a unique patient (Takasuka et al 1998, Kam & Xu 2002, Samaranayake et al 2003. By investigating different C. albicans colonies obtained from healthy volunteers and patients with oral and vaginal candidiasis, Jacobsen et al (2008) reported a higher prevalence of strain microevolution and substitution among healthy volunteers compared to infected patients.…”
mentioning
confidence: 99%
“…(18), and most of them focus on C. albicans (19). In one study, a number of HIV-infected patients enrolled in a longitudinal study of OPC were found to be infected with C. albicans at the beginning of the study and with C. dubliniensis at the end (10).…”
mentioning
confidence: 99%